2018
DOI: 10.4236/oju.2018.82006
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Nephrolithotomy in Obese Patients, Is There Any Challenge?

Abstract: Percutaneous nephrolithotomy (PNL) is a safe and effective procedure in the treatment of large renal stones in obese and non-obese patients with low rate of morbidity and high success rate in different groups of body mass index (BMI), some surgeons believe that morbid obesity increases the risk of complications of PNL, but different recent studies showed there were no significant differences. Objective: To analyze the outcomes of PNL in patients with different BMI and to assess the effects of obesity in the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
0
0
Order By: Relevance
“…Regarding studied patients' personal data; the results of the study reported that nearly three fifths of the studied patients aged from 41 to 50 years old with Mean±SD for the age was 45.38 ± 10.63 years, the reason for this may be related to the fact that prevalence of urinary stones formation increased with aging. This finding is in line with a study carried out by Rashid and Yahya (2018) (18) about "Percutaneous nephrolithotomy in obese patients is there any challenge?" mentioned that, stones affect people in the peak age at onset from 40-59 years old.…”
Section: Discussionsupporting
confidence: 91%
“…Regarding studied patients' personal data; the results of the study reported that nearly three fifths of the studied patients aged from 41 to 50 years old with Mean±SD for the age was 45.38 ± 10.63 years, the reason for this may be related to the fact that prevalence of urinary stones formation increased with aging. This finding is in line with a study carried out by Rashid and Yahya (2018) (18) about "Percutaneous nephrolithotomy in obese patients is there any challenge?" mentioned that, stones affect people in the peak age at onset from 40-59 years old.…”
Section: Discussionsupporting
confidence: 91%